Energy level alignment at organic/inorganic semiconductor heterojunctions: Fermi level pinning at the molecular interlayer with a reduced energy gap. Issue 27 (26th June 2019) - Schlesinger, Raphael; Winkler, Stefanie; Brandt, Matthias; Blumstengel, Sylke; Ovsyannikov, Ruslan; Vollmer, Antje; Koch, Norbert
Abstract : A lying (L) molecular interlayer between ZnO and standing (S) sexiphenyl molecules leads to "concealed" Fermi level pinning. Abstract : The electronic properties of the organic/inorganic semiconductor heterojunction formed by para -sexiphenyl (6P) and three different faces of ZnO are investigated using photoelectron spectroscopy and X-ray absorption. While multilayer molecules stand almost upright with respect to the surface plane, we evidence the presence of a lying 6P interlayer, which exhibits a higher electron affinity. This is due to an energy gap narrowing because of the close vicinity of that interlayer to the higher dielectric constant ZnO and a more planar molecular conformation compared to molecules in the bulk. Both effects have a significant impact on the level alignment mechanisms at the three interfaces, i.e., surface electron push-back and Fermi level pinning. We disentangle the contribution of each effect to the level alignment for both standing and lying 6P layers and show that on ZnO(0001̄) only the push-back contributes, while on ZnO(101̄0) and ZnO(0001) Femi level pinning occurs in addition. In all three cases the lying 6P interlayer establishes the same work function to which the levels of the 6P multilayer align. Only the identification of the complex interplay of level alignment mechanisms and molecular degrees of freedom allows deriving a reliable picture of the energy levels at this heterojunction. This is important as the presence of an interlayer and its modified electronic states might go unnoticed, and conclusions on the correlation between purported interfacial energy levels and functionality of such semiconductor heterojunctions could be misleading.